Effect of temperature on the selection of semiconducting single walled carbon nanotubes using Poly(3-dodecylthiophene-2, 5-diyl). (April 2015) - Gomulya, Widianta; Salazar Rios, Jorge Mario; Derenskyi, Vladimir; Bisri, Satria Zulkarnaen; Jung, Stefan; Fritsch, Martin; Allard, Sybille; Scherf, Ullrich; dos Santos, Maria Cristina; Loi, Maria Antonietta
Abstract: We report on the investigation of the temperature effect on the selective dispersion of single-walled carbon nanotubes (SWNTs) by Poly(3-dodecylthiophene-2, 5-diyl) wrapping. The interaction mechanism between polymer chains and SWNTs is studied by controlling the polymer aggregation via variation of the processing temperature. Optical absorption and photoluminescence measurements including time resolved photoluminescence spectroscopy are employed to study the degree of interaction between the polymer in different aggregation states and the carbon nanotubes. At low processing temperatures, results are consistent with the planarization of the polymer chains and with SWNTs working as seeds for polymer aggregation. The formation of small clusters due to the inter-digitation of alkyl tails between neighboring polymer-wrapped SWNTs allows the formation of the SWNT bundles, as experimentally evidenced and investigated by molecular dynamics simulations. The interaction between the tubes within the bundles, which is reflected in the variation of the photoluminescence dynamics of the polymer, can be suppressed by warming up the sample.